The examined life : how we lose and find ourselves - Grosz, Stephen (New York : W. W. Norton & Company, 2013)
In his work as a practicing psychoanalyst, the author has spent the last twenty-five years uncovering the hidden feelings behind the most baffling human behavior. This book distils more than 50,000 hours of conversation into pure psychological insight without the jargon. At its core, this book is about one ordinary process: talking, listening, and understanding. Its stories unveil a delicate self-portrait of the analyst at work and show how lessons learned in the consulting room can reveal as much to the analyst as to the patient.
Beginnings. How we can be possessed by a story that cannot be told -- On laughter -- How praise can cause a loss of confidence -- The gift of pain -- A safe house -- Telling lies. On secrets -- On not being in a couple -- A passion for ignorance -- On intimacy -- The bigger the front -- Loving. At home -- How paranoia can relieve suffering and prevent a catastrophe -- On the recovery of lost feelings -- Why parents envy their children -- On wanting the impossible -- On hate -- How lovesickness keeps us from love -- Changing. How a fear of loss can cause us to lose everything -- How negativity prevents our surrender to love -- On losing a wallet -- A change in the family -- Why we lurch from crisis to crisis -- On being boring -- On mourning the future -- How anger can keep us from sadness -- On being a patient -- Going back -- On bearing death -- Leaving. Through silence -- On closure -- On waking from a dream.
Includes bibliographical references.
Keywords: Psychoanalysis; Psychology; Psychoanalysis -- Case studies; Psychology -- Case studies; Psychoanalysis; Psychology; Case studies